Pengaruh Pemberian Video Edukasi Perawatan Payudara Terhadap Pengetahuan Ibu Hamil Tm III Dengan Usia Kehamilan 34 -40 Minggu Di Klinik Kartika Jaya Kota Samarinda - Mursidah; Dwi Hartati (PT. Hasba Edukasi Mandiri, 2025)
Background: Breast care during pregnancy is essential for the breastfeeding process. Increasing pregnant women's knowledge can be achieved through health education on breast care using video media. Based on research and questionnaire responses before the provision of video media, 19 respondents (63.3%) had low knowledge about breast care at Kartika Jaya Clinic in Samarinda, indicating a lack of awareness among pregnant women regarding breast care. Objective: To determine the effect of educational video media on breast care knowledge among third-trimester pregnant women. Methods: This study employed a pre-experimental design with a